Removal of a Broken Cannulated Intramedullary Nail: Review of the Literature and a Case Report of a New Technique - Amr A. Abdelgawad; Enes Kanlic (Case Reports in Orthopedics)
Nonunion of long bones fixed with nails may result in implant failure. Removal of a broken intramedullary nail may be a real challenge. Many methods have been described to allow for removal of the broken piece of the nail. In this paper, we are reviewing the different techniques to extract a broken nail, classifying them into different subsets, and describing a new technique that we used to remove a broken tibial nail with narrow canal. Eight different categories of implant removal methods were described, with different methods within each category. This classification is very comprehensive and was never described before. We described a new technique (hook captured in the medulla by flexible nail introduced from the locking hole) which is a valuable technique in cases of nail of a small diameter where other methods cannot be used because of the narrow canal of the nail. Our eight categories for broken nail removal methods simplify the concepts of nail removal and allow the surgeon to better plan for the removal procedure.